IgM anti-GM2 antibodies in patients with multifocal motor neuropathy target Schwann cells and are associated with early onset - Budding, Kevin; Bos, Jeroen W.; Dijkxhoorn, Kim; de Zeeuw, Elisabeth; Bloemenkamp, Lauri M.; Zekveld, Eva M.; Groen, Ewout J.N.; Jacobs, Bart C.; Huizinga, Ruth; Goedee, H. Stephan; Cats, Elisabeth A.; Leusen, Jeanette H.W.; et al. (Journal of neuroinflammation, 2024)
Background Multifocal motor neuropathy (MMN) is a rare, chronic immune-mediated polyneuropathy characterized by asymmetric distal limb weakness. An important feature of MMN is the presence of IgM antibodies against gangliosides, in particular GM1 and less often GM2. Antibodies against GM1 bind to motor neurons (MNs) and cause damage through complement activation. The involvement of Schwann cells (SCs), expressing GM1 and GM2, in the pathogenesis of MMN is unknown. Methods Combining the data of our 2007 and 2015 combined cross-sectional and follow-up studies in Dutch patients with MMN, we evaluated the presence of IgM antibodies against GM1 and GM2 in serum from 124 patients with MMN and investigated their binding to SCs and complement-activating properties. We also assessed the relation of IgM binding and complement deposition with clinical characteristics. Results Thirteen out of 124 patients (10%) had a positive ELISA titer for IgM anti-GM2. Age at onset of symptoms was significantly lower in MMN patients with anti-GM2 IgM. IgM binding to SCs correlated with IgM anti-GM2 titers. We found no correlation between IgM anti-GM2 titers and MN binding or with IgM anti-GM1 titers. IgM binding to SCs decreased upon pre-incubation of serum with soluble GM2, but not with soluble GM1. IgM anti-GM2 binding to SCs correlated with complement activation, as reflected by increased C3 fixation on SCs and C5a formation in the supernatant. Conclusion Circulating IgM anti-GM2 antibodies define a subgroup of patients with MMN that has an earlier onset of disease. These antibodies probably target SCs specifically and activate complement, similarly as IgM anti-GM1 on MNs. Our data indicate that complement activation by IgM antibodies bound to SCs and MNs underlies MMN pathology.